Exploring stress tolerance indices to identify terminal heat tolerance in spring wheat in Nepal - Puri, Ramesh Raj; Gautam, Nutan Raj; Joshi, Arun Kumar (Journal of Cereal Research, 2025)
Terminal heat stress during anthesis and grain filling period accelerates maturity and significantly reduces grain size and weight. A study was performed to explore stress tolerance indices that can judge terminal heat tolerance in spring wheat in Nepal. Ten diverse lines were planted under normal (non-stress) and late (heat stress) sown condition at two locations (Parwanipur and Hardinath) in Nepal. The trial was set up in Alpha Lattice design with two replications in two consecutive crop cycles 2011-12 and 2012-13. Yield traits were recorded and stress susceptibility and tolerant indices were estimated. Correlation analysis showed that yield under stress environment had positive (r=0.80) and significant (p<0.05) association with that under non-stress environment. Similarly, grain yield under both environments had significant and positive correlation with mean productivity (MP), geometric mean productivity (GMP) and heat tolerance index (HTI) whereas non-significant correlation with stress susceptibility index (SSI) and tolerance index (TOL). The first two principal components explained 97% of the variation. Biplot analysis revealed that stress tolerance indices can be used selection criteria for identification of heat tolerant genotypes. Combined analysis showed that NL 1140 (SSI=0.71) possessed highest tolerance, followed by BL 3978 (SSI=0.79) while NL 1096 (SSI=1.5) appeared least tolerant. The most tolerant line NL 1140 produced mean yield of 3730.5 Kg/ha and 3000.3 Kg/ha under normal and late sown condition, respectively. The TOL of this line was the best (730) among the tested genotypes. NL 1140 and BL 3978 were identified as promising for terminal heat tolerance and can be used directly as well as in the crossing program to breed heat tolerant genotypes. Â Â